Predictors and Utilization of Health Institution Services for Childbirth among Mothers in a Southern Nigerian City. (7th December 2021) - Arogundade, Kazeem; Sampson, June; Boath, Elizabeth; Akpan, Ubong; Olatoregun, Olaposi; Femi-Pius, Oluwayemisi; Orjih, Jude; Afirima, Barinaadaa; Umar, Nasir
Abstract : Background . Poor maternal health indices, including high maternal mortality, are among Nigeria's major public health problems. Most of these deaths can be prevented by timely access and utilization of maternity healthcare services by women. Aim/Objective . This study seeks to identify factors affecting the utilization of health facilities for the delivery of babies among mothers in Calabar, Cross River State, Nigeria. Methodology . The study was a community-based cross-sectional study. A structured questionnaire was administered to 422 women of reproductive age residents in the study area who had given birth at least once within the last five years prior to the survey using a multistage random sampling technique. Data generated were entered, coded, and analyzed using Statistical Packages for Social Sciences (SPSS version 22.0), and results were presented in tables and charts. Chi-squared tests and multiple logistic regression were used for the identification of variables associated with health facility-based delivery. Result . The mean age of respondents was 27.3 years (SD = 8.4). Fifty-two percent of the respondents utilized the health facility for delivery, 89.6% attended at least one antenatal clinic (ANC), and 18.9% completed at least 3 ANC sessions. There was a statistically significant association between health facility delivery and marital status (P = 0.007 ), education (P = 0.042 ), and family size (P = 0.002 ). Older women (OR = 0.7, CI = 0.169–3.714), Christians (OR = 1.9, CI = 0.093–41.1), divorcees (OR = 3.7, CI = 0.00–0.00), and respondents who registered early (first trimester) for ANC (OR = 4.9, CI = 0.78–31.48) were found to be higher users of delivery services at the health facility. Conclusion . Community health intervention focusing on improving the knowledge and awareness of the significance of utilizing available delivery services at the healthcare facility should be developed and implemented.